2015
DOI: 10.1515/amm-2015-0263
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Of 6xxx Series Aluminium Alloys

Abstract: The hot deformation behavior of the 6xxx aluminum alloys was investigated by compression tests in the temperature range 100• C-375• C and strain rate range 10 −4 s −1 and 4x10 −4 s −1 using dilatometer DIL 805 BÄHR Thermoanalyse equipped with accessory attachment deformation allows the process to execute thermo-plastic in vacuum and inert gas atmosphere. Associated microstructural changes of characteristic states of examined alloys were studied by using the transmission electron microscope (TEM). The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Meanwhile, the variations of the frequency of [10][11][12][13][14][15] o grain boundaries with the variations of thermo-deformation parameters are not obvious. Because the CDRX mechanism often results in the increased frequency of [10][11][12][13][14][15] o grain boundaries, it can be concluded that the major dynamic recrystallization mechanism of the studied superalloy is DDRX. Fig.…”
Section: Flow Softening Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the variations of the frequency of [10][11][12][13][14][15] o grain boundaries with the variations of thermo-deformation parameters are not obvious. Because the CDRX mechanism often results in the increased frequency of [10][11][12][13][14][15] o grain boundaries, it can be concluded that the major dynamic recrystallization mechanism of the studied superalloy is DDRX. Fig.…”
Section: Flow Softening Behaviormentioning
confidence: 99%
“…It is well known that a comprehensive analysis of flow softening behavior is significant to achieve excellent properties of alloys. In recent years, the flow softening behaviors of magnesium alloys [4,5], titanium alloys [6,7,8,9], aluminum alloys [10,11], and some other alloys [12,13,14] have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Then it can be written for the process undergoes at constant strain rate as described in Eq. (3) (Mrówka-Nowotnik et al, 2015):…”
Section: Resultsmentioning
confidence: 99%
“…Then it can be written for the process undergoes at constant strain rate as described in Eq. () (Mrówka‐Nowotnik et al ., 2015): truerightlnε̇T1=left1×lntrueε̇ln()sinhfalse(ασ)Tleft1em×ln()sinhfalse(ασ)T1ε̇=QRT…”
Section: Resultsmentioning
confidence: 99%
“…In the case of aluminum alloys, 2xxx and 6xxx alloys are the most commonly used in the process of precipitation hardening. The precipitation sequence of 6xxx alloys, where the major alloying elements are Mg and Si, is as follows [1][2][3][4]…”
Section: Introductionmentioning
confidence: 99%